2018
DOI: 10.1123/jmld.2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Visual Illusions Affect Motor Performance, But not Learning in Highly Skilled Shooters

Abstract: Enhanced expectancies are an important component of OPTIMAL theory and are thought to contribute to motor performance and learning. There is limited information, however, on the generalizability of OPTIMAL theory to highly skilled individuals. The purpose of this study was to examine the effects of visual illusions, specifically an Ebbinghaus illusion, on the performance and learning of an aiming task using highly skilled 10-m rifle and pistol shooters. Two groups of shooters with international experience were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
0
11
1
Order By: Relevance
“…Lastly, in an airsoft shooting task, Bahmani et al (2017) tested internationally competitive airsoft shooters and found greater self-efficacy and accuracy for targets with a small surround compared to those with a large surround (i.e., better performance for perceptually larger targets), but no retention of these effects in a 24-hour follow-up.…”
Section: Ebbinghaus Illusion and Actions At A Distancementioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, in an airsoft shooting task, Bahmani et al (2017) tested internationally competitive airsoft shooters and found greater self-efficacy and accuracy for targets with a small surround compared to those with a large surround (i.e., better performance for perceptually larger targets), but no retention of these effects in a 24-hour follow-up.…”
Section: Ebbinghaus Illusion and Actions At A Distancementioning
confidence: 99%
“…Recent research has extended these questions to sporting contexts such as golf-putting, marble shooting, and competitive shooting (Bahmani et al, 2017;Cañal-Bruland et al, 2016;Chauvel et al, 2015;Maquestiaux et al, 2020;Witt et al, 2012;Wood et al, 2013). Unlike prior research, the kind of motor movements performed in these studies involve manipulating an object to contact a target.…”
Section: Ebbinghaus Illusion and Actions At A Distancementioning
confidence: 99%
“…Enhanced expectancies can also be achieved by manipulating an individual's perception of task difficulty such that it is perceived easier [11,12,32,34,163,231] and/or altering the criterion for success by providing easier objectives earlier in practice [213]. For instance, youth and adult target-aiming performance and learning is improved when participants aim towards a target that appears larger by surrounding it with smaller targets to manipulate the perception of its size [11,12,34,163]. However, similar to the caution required if implementing social-comparative feedback, the potentially beneficial motor performance/learning effects when providing false positive feedback and/or manipulating perceptions of task difficulty requires consideration.…”
Section: Pillar 1: Enhanced Expectanciesmentioning
confidence: 99%
“…ACL injury can also lead to fear of (re)injury-the most commonly cited reason among athletes who do not return to play [76]-potentially leading to increased muscular tension, fatigue, decreased coordination, and as a result, higher vulnerability to future injury [3]. As these psychological factors regarding perceived ability are critical for an athlete's successful return to sport [66,86], it is noteworthy that enhancing expectancies can improve self-efficacy [7,8] and could potentially reduce fear of (re)injury.…”
Section: Enhanced Expectancies and Clinical Applications Using Instruction-based Feedbackmentioning
confidence: 99%
“…For instance, during a single leg hop a clinician could safely place a cone at a distance perceived as "easy" to reach by the patient to enhance self-efficacy before increasing the perceived distance the patient strives to jump to. As an illustrative example with respect to youth play, instructors could even adopt the "Ebbinghaus Illusion" that can enhance self-efficacy and motor behavior by making targets appear larger than they actually are [7,8,19,82]. For instance, this principle could be used in youth by creating "perceptually larger targets" an athlete must kick a soccer ball towards; small objects could surround a goal target to make it appear larger.…”
Section: Enhanced Expectancies and Clinical Applications Using Instruction-based Feedbackmentioning
confidence: 99%